1979
DOI: 10.1159/000194035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metabolite VIII of Bromexine (Na 872) on Type II Epithelium of the Lung

Abstract: 50 Wistar rats were divided into 5 groups: 4 experimental and 1 control group. The experimental groups A and B received, per os, a daily dose of 100 mg of Na 872 (metabolite VIII of Bromexine) for 3 or 6 days and were killed 1 day later. The experimental groups C and D received 200 mg of the same substance according to the same experimental procedure and for the same periods. The lungs were fixed in situ by perfusion, examined by light and electron microscopy using morphometric methods. No manifest lesions occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1983
1983
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The loss of alveolar patency definitely alters the balance of alveo lar-capillary gas exchanges, thus fostering the devel opment of respiratory failure. Numerous preclinical and clinical studies [23][24][25][26][27][28][29][30][31][32][33] have demonstrated the ef ficacy of ambroxol for both stimulating pulmonary surfactant synthesis and inhibiting its catabolism. The results of the present study agree with those reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of alveolar patency definitely alters the balance of alveo lar-capillary gas exchanges, thus fostering the devel opment of respiratory failure. Numerous preclinical and clinical studies [23][24][25][26][27][28][29][30][31][32][33] have demonstrated the ef ficacy of ambroxol for both stimulating pulmonary surfactant synthesis and inhibiting its catabolism. The results of the present study agree with those reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Ambroxol [trans-4-(2-amino-3,5-dibromobenzylamino)-cyclohexane hydrochloride] (AMB) is a bromhexin metabolite. Although the functional mechanism of AMB is still unknown, AMB is reported to stimulate the synthesis and secretion of surfactant in type 2 alveolar epithelium [22]and to scavenge oxidants [23]. Both agents have been widely used as mucolytic drugs in the treatment of lung diseases, despite the differences between their chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Ambroxol, a bromhexine derivative able to induce surfactant synthesis by alveolar type-2 cells [9], represents a good tool for in vivo study of the influence of surfactant stimulation in normal and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%